2019
DOI: 10.1002/adfm.201907437
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Waterproof Resistive Random‐Access Memory Based on Nitrocellulose for Skin‐Attachable Wearable Devices

Abstract: Memory for skin-attachable wearable devices for healthcare monitoring must meet a number of requirements, including flexibility and stability in external environments. Among various memory technologies, organic-based resistive random-access memory (RRAM) devices are an attractive candidate for skin-attachable wearable devices due to the high flexibility of organic materials. However, organic-based RRAMs are particularly vulnerable to external moisture, making them difficult to apply as skin-attachable wearable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…Extensive studies have revealed that organic small molecules could be applied as excellent resistive memory materials, attributing to their advantages of low cost, light weight, mechanical flexibility, and ease of processing 47,48,66,70,83‐104 . Many organic small molecules have been reported to exhibit resistive switching characteristics, including the binary and even higher multilevel nature 70,83‐96,105,106 .…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have revealed that organic small molecules could be applied as excellent resistive memory materials, attributing to their advantages of low cost, light weight, mechanical flexibility, and ease of processing 47,48,66,70,83‐104 . Many organic small molecules have been reported to exhibit resistive switching characteristics, including the binary and even higher multilevel nature 70,83‐96,105,106 .…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%
“…In addition, their optoelectronic properties can be easily modulated by molecular design‐cum‐synthesis strategy, which opens up possibilities of achieving diverse memory functions 41‐44 . Their intrinsic flexibility and softness also endow them superior ability for stretchable and wearable electronics, 45‐47 which can bring us closer to the future artificial intelligent lifestyle. Thanks to these charming advantages, numerous research efforts have been devoted to seeking for high‐performance organic‐based data storage materials and devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, most of the switching behaviors of RRAM devices have been investigated through electrical measurements and simulation approaches, resulting in an insufficient understanding of their fundamental science. [26][27][28] Therefore, a novel technique for the investigation of the switching mechanism is urgently needed. High-resolution transmission electron microscopy (HRTEM) possesses high spatial resolution and reveals microstructure at the atomic scale, providing direct evidence of relations between performance and microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, a novel nitrocellulose passivation layer is suggested for improving the stability of MoS 2 TFTs. Nitrocellulose is an organic material conventionally used as a bandage to protect wounds on the skin, as a lacquer, as nail polish, and as a material for protecting other materials due to its high waterproof characteristic, high flexibility, and biocompatibility [12]. Unlike the previous studies, the proposed passivation layer does not need vacuum equipment, high-temperature deposition, and a complex fabrication process.…”
Section: Introductionmentioning
confidence: 99%